Оn some problems of neural network technologies in electric components diagnosing - Telenyk, S.F.; Savchuk, O.V.; Pocrovskyi, E.O.; Morgal, O.M.; Krivenko, K.S.; Latash, I.O. (Штучний інтелект, 2017)
The paper describes an idea of getting electric components diagnostic information and its transformation using the discrete Karhunen-Loeve expansion. Presorting of elements by their physical and technical states is proposed to operate with the MLP, self-organized and RBF- neural networks in the MATLAB environment. The paper investigates the possibility of using neural network technologies for improving electric components diagnosing by integral effects for increasing reliability of complex technological systems. The statistical and individual classification and presorting of elements according to their physical and technical states for work with the use of neural network technologies is proposed. У статті описується ідея отримання діагностичної інформації про електричні компоненти та її перетворення за допомогою дискретного розкладання Карунена-Лоева. Запропоновано визначення фізичних та технічних станів елементів за допомогою MLP, самоорганізованих та RBF-нейронних мереж в середовищі MATLAB. У роботі досліджується можливість використання нейронних мережевих технологій для поліпшення діагностики електричних компонент за інтегральними ефектами для підвищення надійності складних технологічних систем. Запропоновано статистичну та індивідуальну класифікацію та сортування елементів відповідно до їх фізичних і технічних станів для роботи з використанням нейронних мережевих технологій.